2015
DOI: 10.1001/jamaoto.2014.3584
|View full text |Cite
|
Sign up to set email alerts
|

Angiosarcoma of the Scalp and Face

Abstract: Multimodality therapy for angiosarcoma is associated with improved LRC, RFS, and OS. Younger patients with resectable disease undergoing multimodality therapy for angiosarcoma had the best clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
156
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(178 citation statements)
references
References 19 publications
10
156
1
3
Order By: Relevance
“…The prognostic significance of age on the outcome of HNCAS is controversial. Patel et al 11 reported that patients younger than 70 years fared better with improved locoregional control and relapse-free survival than older patients. Although age is not a confirmed prognostic factor, advanced age often precludes patients from curative therapy due to concomitant chronic diseases or general debility.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The prognostic significance of age on the outcome of HNCAS is controversial. Patel et al 11 reported that patients younger than 70 years fared better with improved locoregional control and relapse-free survival than older patients. Although age is not a confirmed prognostic factor, advanced age often precludes patients from curative therapy due to concomitant chronic diseases or general debility.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Table 3, five of six studies support the beneficial role of RT. 4,[6][7][8]10,11 Guadagnolo et al 7 advocated simple resection of the gross tumour to facilitate noncomplicated reconstruction and thus expedite RT. Two-staged surgery was discouraged.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…guns fatores têm sido associados com um risco aumentado para o angiossarcoma, como a exposição prévia à radiação, o linfedema crônico (síndrome de Stewart-Treves) e a exposição a produtos químicos. 3 A forma mais comum do angiossarcoma é a cutâ-nea, tipicamente acometendo cabeça e pescoço,…”
Section: Introductionunclassified
“…1,2 Al-predominando no couro cabeludo de homens idosos caucasianos. [1][2][3][4] Está associado a altas taxas de recorrência e a um mau prognóstico, apesar do tratamento. 2 Com o objetivo de demonstração clínica desse raro tumor, relatamos um caso de angiossarcoma do couro cabeludo, enfatizando a sua agressividade e a importância do diagnóstico precoce.…”
Section: Introductionunclassified